Impact exerted by scaffolds and biomaterials in periodontal bone and tissue regeneration engineering: new challenges and perspectives for disease treatment - Simona Santonocito; Salvatore Ferlito; Alessandro Polizzi; Vincenzo Ronsivalle; Giuseppe Reitano; Antonino Lo Giudice; Gaetano Isola (Open Exploration Publishing Inc., 2023)
The periodontium is an appropriate target for regeneration, as it cannot restore its function following disease. Significantly, the periodontium's limited regenerative capacity could be enhanced through the development of novel biomaterials and therapeutic approaches. Notably, the regenerative potential of the periodontium depends not only on its tissue-specific architecture and function but also on its ability to reconstruct distinct tissues and tissue interfaces, implying that the development of tissue engineering techniques can offer new perspectives for the organized reconstruction of soft and hard periodontal tissues. With their biocompatible structure and one-of-a-kind stimulus-responsive property, hydrogels have been utilized as an excellent drug delivery system for the treatment of several oral diseases. Furthermore, bioceramics and three-dimensional (3D) printed scaffolds are also appropriate scaffolding materials for the regeneration of periodontal tissue, bone, and cartilage. This work aims to examine and update material-based, biologically active cues and the deployment of breakthrough bio-fabrication technologies to regenerate the numerous tissues that comprise the periodontium for clinical and scientific applications.